MODELLING FINANCIAL PERFORMANCE OF FOOD AND BEVERAGES COMPANIES LISTED ON NIGERIAN EXCHANGE GROUP: THE FIRM CHARACTERISTICS EFFECT (Journal of Global Accounting, 2023)
The financial performance of food and beverages firms in Nigeria dwindle especially when they are unable to effectively combine their experience over the ages, asset base and debt resources in a way that yields profitable returns. The study determines the effect of firm characteristics on the financial performance of listed food and beverages firms in Nigeria. The study intends to ascertain the extent to which firm size, firm age and firm leverage affect the return on assets of listed food and beverages firms in Nigeria. Ex-post facto research design was deployed in the study. Purposive sample of five (5) listed food and beverages firms was used in the study. Secondary data were obtained from the annual reports of sampled companies from 2012 to 2021 reporting periods. Panel least square regression using Fixed Effect Model was utilised in estimating the regression results at 5% level of significance. The findings showed that although Firm size had no significant but positive effect on the return on assets of listed food and beverages firms in Nigeria, Firm age and Firm leverage had a significant but negative effect on the return on assets of listed food and beverages firms in Nigeria; The study conclude that sound firm characteristics basically show the extent of financial performance of firms because they are indices of how effective and efficient the management makes use of firms’ available resources. It was recommended that food and beverages firms should increase their asset base in order to have the wherewithal to commit their available resources to more investment opportunities; Older firms should where necessary change their systems to cope with the new environmental conditions, innovation and advancement in order to avoid being rigid, which worsens the firms’ financial performance. It was also recommended that there should be a well-planned capital structure in the food and beverages firms in order to prevent risk of insolvency, increase business value, maximize shareholders' wealth, and reduce cost of capital among firms.
Keywords: Firm Age; Firm Characteristics; Firm Leverage; Firm Size; Return on Assets